Edukasi Hukum Perlindungan Konsumen bagi Masyarakat Perumahan Kelapa Sawit Marpoyan Damai Pekanbaru Tahun 2026 - Ramanitya Dewi Putri; Rani Aulia Rayusda; Nisah Ayu Siregar; Yasti Sari; Yola Putri Anggraini; Kardi Kardi; Vika Vika; Dian Pariska; Stevanus Antoni.R; Ayuthia Ramadhani Herman; Anne Monika Fristy (FKIP, Universitas Palangka Raya, 2026)
Consumer protection is an essential aspect of a fair and democratic legal system. However, low public awareness, limited access to information, and the increasing complexity of digital transactions remain major challenges in enforcing consumer rights. This community service program aims to improve public legal awareness and practical skills in protecting consumer rights through an integrated legal education approach. The program was implemented through interactive legal counseling, real-case simulations, and digital educational modules that participants could access independently. Participants included members of the community, e-commerce users, secondary school students, and vulnerable groups, including students with special needs. The results showed significant improvements in participants’ understanding of consumer rights and obligations, their ability to recognize unfair business practices, and their skills in preparing consumer complaints. The integration of local and international perspectives, particularly related to digital transactions, enhanced participants’ understanding of global consumer protection standards. Digital media also supported continuous learning and the development of a legally aware consumer community. The program demonstrates that participatory, inclusive, and practice-oriented legal education is effective in strengthening consumer protection in Indonesia.